Asystole associated with cluster headache - (:unkn) unknown (ELSEVIER SCIENCE INC, 2004)
A 43-year-old man with asystole and syncope occurring during cluster headache attacks is reported. The asystole and syncope attacks disappeared completely following prophylactic therapy with methysergide maleate. To the authors' knowledge, the present case is unique in associating asystole with cluster headache attacks and may be due to hyperactivity of the parasympathetic system.
Keywords: asystole; cluster headache; syncope; PRESSURE; RHYTHM